The Rising Tide: Disparities in Fentanyl-Related Mortality Among Hispanic and Non-Hispanic Adolescents and Young Adults in the United States - Paige Brinzo; Adrienne Dean; Ayden Dunn; Diana Lobaina; Sebastian Densley; Panagiota Kitsantas; Maria Carmenza Mejia; Lea Sacca (Youth)
Objectives: The United States has been greatly impacted by the opioid overdose epidemic, and fentanyl has largely contributed to the rise in overdose deaths in the past decade. We have analyzed trends in fentanyl-related mortality amongst adolescents and young adults (AYAs) to further describe emerging trends by ethnicity, gender, and age. Methods: We used mortality data from the U.S. Centers for Disease Control and Prevention Wide-Ranging Online Data for Epidemiologic Research (WONDER) Multiple Cause of Death file from 2009 to 2022. Drug overdose mortalities were identified using International Classification of Diseases, Tenth Revision (ICD-10) codes. Joinpoint regression was used to examine mortality rates involving fentanyl by ethnicity (Hispanic and non-Hispanic), gender, and age category. Results: The Average Annual Percent Change (AAPC) for fentanyl-involved mortality increased for all adolescents and young adults within the United States from 2009 to 2022. The greatest AAPCs for fentanyl-related mortalities occurred amongst, Hispanic AYAs, Male AYAs, and 13–18-year-olds. Conclusions: Significant increases in fentanyl-related mortalities have occurred in AYAs from 2009 to 2022. Disparities by ethnicity and emerging trends in gender and age category highlight the need for targeted approaches to help aid in reducing fentanyl-involved mortality amongst AYAs. There is an urgent need for harm reduction and public health efforts to address this escalating crisis.